A Cluster-Based Secure Synchronization Protocol for Underwater Wireless Sensor Networks. (7th April 2014) - Xu, Ming; Liu, Guangzhong; Zhu, Daqi; Wu, Huafeng
Abstract : Secure time synchronization is one of the key concerns for Underwater Wireless Sensor Networks (UWSNs). This paper presents a CLUster-based Secure Synchronization (CLUSS) protocol that ensures the security of synchronization under harsh underwater environments against various attacks, including Sybil attack, replay attack, message manipulation attack, and delay attack. The time synchronization process of CLUSS is divided into three phases: authentication phase, intercluster synchronization phase, and intracluster synchronization phase. During the authentication phase, cluster heads are authenticated to beacons and ordinary nodes are authenticated to cluster heads. During the process of intercluster and intracluster synchronization phases, CLUSS distinguishes the propagation delay of downlink from that of uplink caused by node movement in order to improve time synchronization accuracy. Moreover, part of these two phases can be executed concurrently for reducing the number of messages generated in synchronization. We demonstrate through simulations that CLUSS can reduce synchronization errors as well as energy consumption compared to traditional protocols in various circumstances.